A Robust Approach for Reproducing the Haptic Sensation of Sandpaper With Different Roughness During Bare Fingertip Interaction - Zhang, Jianyao; Kajimoto, Hiroyuki (Frontiers in Virtual Reality, 2022)
When reproducing realistic virtual textures for bare finger interaction, an accelerometer attached to a fingernail is commonly used. This measurement depends on the dynamic conditions during the exploration action, and slight differences in roughness are difficult to acquire accurately because of masking by shivering, low-pass filtering by the finger tissue, and sensor accuracy. We propose a simpler yet robust approach based on the 3D measurement of the surface and compare it with the conventional approach. The 3D surface images of sandpaper with different degrees of roughness were captured using a 3D microscope, and the line roughness curve was transformed into an acceleration curve by quadratic differential transformation. The real-time acceleration and frictional force were measured by an accelerometer and force sensor for comparison. A haptic device replaying acceleration-based vibrations by two audio speakers and producing tangential force by a motor-controlled liner slide was developed for reproduction. We conducted experiments with participants to evaluate the reproduction approach. Experimental results showed that the conventional approach obtained sufficient discriminability with the assistance of force, whereas the proposed approach achieved higher reproducibility and discriminability by sole vibration. Thus, our approach provides a new reference for studies of bare finger interaction with rough surfaces.